2022
DOI: 10.1186/s43163-022-00335-6
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma associated with an active cutaneous leishmaniasis in immunocompetent patient: case presentation of an unlikely association and literature—review

Abstract: Background Association between leishmaniasis and malignancy can be classified into four categories: leishmaniasis mimicking malignancy, leishmaniasis co-existing with malignancy, malignancy developing in patients with leishmaniasis scar, and leishmaniasis developing in patients with malignancy. In immunocompetent patients, the main form of association is cutaneous squamous cell carcinoma (cSCC) developing within cutaneous leishmaniasis scar years after cutaneous leishmaniasis is cured. Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An unlikely association of squamous cell carcinoma with an active cutaneous leishmaniasis was reported in an immunocompetent human patient [25], and a report of a case of basal cell carcinoma (Clark level IV) that had been developed on characteristic active lesion of mucocutaneous leishmaniasis, suggesting that carcinogenesis, in this case, was triggered by Leishmania parasites and induced by sun's ultraviolet (UV) radiation exposure [56]. Although causality is still to be proved, a biopsy may be essential to rule out associated skin malignancy in reluctant cutaneous leishmaniasis [25]. A report of a solitary cutaneous leiomyoma mimicking leishmaniasis demonstrates that neoplasms mimicking cutaneous leishmaniasis are an alert for an appropriate differential diagnosis [57].…”
Section: Tumor and Leishmania Infection Associationmentioning
confidence: 94%
See 2 more Smart Citations
“…An unlikely association of squamous cell carcinoma with an active cutaneous leishmaniasis was reported in an immunocompetent human patient [25], and a report of a case of basal cell carcinoma (Clark level IV) that had been developed on characteristic active lesion of mucocutaneous leishmaniasis, suggesting that carcinogenesis, in this case, was triggered by Leishmania parasites and induced by sun's ultraviolet (UV) radiation exposure [56]. Although causality is still to be proved, a biopsy may be essential to rule out associated skin malignancy in reluctant cutaneous leishmaniasis [25]. A report of a solitary cutaneous leiomyoma mimicking leishmaniasis demonstrates that neoplasms mimicking cutaneous leishmaniasis are an alert for an appropriate differential diagnosis [57].…”
Section: Tumor and Leishmania Infection Associationmentioning
confidence: 94%
“…However, most of the evidence about the association between cutaneous leishmaniasis and skin cancer is still based on case reports and other clinical observations rather than strong epidemiological observational studies [55]. An unlikely association of squamous cell carcinoma with an active cutaneous leishmaniasis was reported in an immunocompetent human patient [25], and a report of a case of basal cell carcinoma (Clark level IV) that had been developed on characteristic active lesion of mucocutaneous leishmaniasis, suggesting that carcinogenesis, in this case, was triggered by Leishmania parasites and induced by sun's ultraviolet (UV) radiation exposure [56]. Although causality is still to be proved, a biopsy may be essential to rule out associated skin malignancy in reluctant cutaneous leishmaniasis [25].…”
Section: Tumor and Leishmania Infection Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…During this study, it was observed that the reactivation of EBV occurred and displayed a high load of 3000 genome equivalents per ml (geq/ml), which was further reduced upon treatment with rituximab (Agteresch et al 2007 ). Several studies have shown that tumor generation occurs in Leishmania-infected individuals (Schwing et al 2019 , Ouattassi et al 2022 , Vega-Benedetti et al 2022 ). However, oncogenic EBV involvement remain unexplored in these tumors.…”
Section: Ebv Reactivation By Protozoamentioning
confidence: 99%